Persepsi Mahasiswa Ilmu Komunikasi Dalam Implementasi Program Merdeka Belajar Kampus Merdeka (MBKM) Pada Universitas Mbojo Bima - Hermanto, Lubis; Rosadi, Ariani; Kurniawan, Dandi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Increased competitiveness and increased capacity is urgently needed to catch up with other countries in the world. One way is to take advantage of technology that is currently growing rapidly. With various innovations and creative ideas, it is hoped that we will be able to catch up with other nations. Therefore, this is an opportunity for us, especially universities, to innovate in learning. It is hoped that the Independent Campus Learning Policy (MBKM) will be the answer to these demands. The Merdeka Campus is an autonomous and flexible form of learning in tertiary institutions so as to create a learning culture that is innovative, not restrictive, and in accordance with the needs of students. Various forms of learning activities outside college, including doing internships or work practices in industry or other workplaces, carrying out community service projects in villages, teaching in education units, participating in student exchanges, conducting research, conducting entrepreneurial activities, making studies/ independent projects, and participate in humanitarian programs. All these activities must be carried out with the guidance of the lecturer. The independent campus is expected to be able to provide field contextual experiences that will improve student competency as a whole, be ready for work, or create new jobs. the implementation of the MBKM Program at Mbojo Bima University has been effective and maximal in terms of the results of the implementation of the program and the changes in students after participating in both soft skill and hard skill programs. Therefore, it can be said that the implementation of the MBKM program at Mbojo Bima University in the Communication Studies Study Program has been carried out based on the instructions.Keywords: Perception, Implementation, Independent Campus Learning Program (MBKM)